Case reportCutaneous larva migrans syndrome: a case report - Tekely, Emilia; Szostakiewicz, Beata; Wawrzycki, Bartłomiej; Kądziela-Wypyska, Grażyna; Juszkiewicz-Borowiec, Maria; Pietrzak, Aldona; Chodorowska, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Cutaneous larva migrans (CML) is a frequent parasitic infestation caused by migration of animal hookworm larvae into the human epidermis. This skin disease is common in warmer climates among people, who have contact with contaminated soil. Clinical manifestation of CML is an itchy, erythematous, linear tract, which appears days to even months after exposure to infested sand or soil. Diagnosis is established on the clinical presentation. We describe a case of CML acquired during a holiday in Brazil.